Strategi Adaptasi Masyarakat Lokal di Kawasan Tempat Penampungan Akhir Sampah Kota Padang - Ananda, Nofrian Reski; Irwan, Irwan; Firadus, Firdaus (Jurnal Intervensi Sosial dan Pembangunan, 2025)
The amount of waste in Padang City is estimated at 240 tons per day. Besides that, the number of TPAs from 1989 until now is only 1 TPA. This results in a buildup of rubbish, which emits a smell that disturbs the local community. This research aims to analyze the adaptation strategies of local communities in the final waste storage area in Aia Winter Village, Koto Tangah District, Padang City, West Sumatra. The theory used in this research is the adaptation strategy theory proposed by John William Bennett. This research uses qualitative research methods with descriptive research type. Informant withdrawal was carried out using purposive sampling techniques. The data collection method in this research began with observation, interviews and document study. Data analysis techniques are carried out in several stages, namely, data collection, data reduction, data presentation and drawing conclusions. The research results show that there are 3 adaptation strategies carried out by the community around the waste landfill. These three adaptation strategies are related to adaptation behavior which is used by providing room freshener to avoid the smell caused by rubbish. Furthermore, the community uses strategic strategies to avoid the smell caused by rubbish by planting trees or reforestation. The adaptation process strategy is also carried out by local communities by using fly or insect traps and using waste that is still suitable for use. The novelty of the research is an environment-based adaptation strategy. Keywords: Strategy Adaptation, Local Community, TPA.